Bone Marrow Edema Syndrome of the Foot and Ankle: Mid- to Long-Term Follow-up in 18 Patients. Issue 3 (June 2016) - Singh, Dishan; Ferrero, Andrea; Rose, Barry; Goldberg, Andrew; Cullen, Nicholas
Bone marrow edema syndrome (BMES) is a condition characterized by pain and an increase interstitial fluid within the bone marrow in the absence of a definable cause. The purpose of this study was to assess the changes in the pattern of bone edema and quality of pain over time. In patients diagnosed with BMES of the foot and ankle, we investigated the benefit of treatment with bisphosphonates and immobilization in a pneumatic walking boot compared with immobilization in a boot alone. This study is a retrospective review of 18 consecutive patients (mean age 54 years) diagnosed with foot and ankle BMES. Twelve (67%) patients were female and 6 were male with a mean age of 60.1 and 43.0 years, respectively (P < .05). The minimum follow-up was 2 years (range 2-11 years, mean 5.75 years). Five females and no males were found to suffer from generalized osteoporosis. The average duration of symptoms prior to presentation was 22 weeks and the most common bone affected was the talus (56%). More than one bone was affected in 8 (44%) patients. All patients were given a walking boot at first attendance for 8 weeks. The mean time to resolution of pain in patients treated with a pneumatic walker alone (7 patients) was 25.6 weeks (range 8-36 weeks). In the 11 patients whose pain had not improved at their first follow-up, treatment with bisphosphonates led to a more rapid resolution of pain in 13.8 weeks if given intravenously, and 24.0 weeks if given orally. Statistical analysis demonstrated a significant advantage in using a bisphosphonate versus a protected weightbearing alone (P < .01). Recurrence within the same foot and ankle occurred in 44% of patients at a mean interval of 15.6 months and migration to a different site occurred in 6% of patients. Levels of Evidence: Therapeutic, Level III: Retrospective, comparative trial